2014
DOI: 10.2147/jmdh.s51359
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with visual impairment in Ibadan: a clinical study in primary care

Abstract: BackgroundVisual function is important for optimal orientation in functional and social life, and has an effect on physical and emotional well-being. Visual impairment, therefore, leads to restrictions in all aspects of daily living and is related to quality of life. The aim of this study was to provide information on the causes of visual impairment in patients presenting to their family physician, the spectrum of impairment, and its impact on quality of life for these patients.MethodsThis descriptive cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 19 publications
2
19
3
1
Order By: Relevance
“…is might result from most older people considering that visual loss is to be expected in later life and think that nothing can be done to improve the situation. is result is consistent with other studies [3,15,16]. is might be due to that various age-related ocular disorders result in a decline in visual function, and thus have significant effects on patients' VRQOL [17,18].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…is might result from most older people considering that visual loss is to be expected in later life and think that nothing can be done to improve the situation. is result is consistent with other studies [3,15,16]. is might be due to that various age-related ocular disorders result in a decline in visual function, and thus have significant effects on patients' VRQOL [17,18].…”
Section: Discussionsupporting
confidence: 92%
“…Overall the proportion of poor VRQOL in this study was 49.2% (95% CI: 44.2%-53.3%). is result is higher than that in studies conducted in Ibadan, Nigeria (21.5%) [3]. is might be due to the small sample size of patients with visual impairment.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…There has yet to be a global assessment of the impact of eye health, including vision impairment, eye disease and ophthalmic interventions on quality of life across the lifespan, despite the growing number of ophthalmic studies assessing quality of life, and increased value placed on patient-reported outcomes. Prior studies on vision and quality of life have usually focused on specific countries (eg, USA, 24 Finland, 25 South Korea, 26 Nigeria 27 ), populations (eg, Malay population in Singapore, 28 Latino population 29 and indigenous peoples of the Americas 30 in the USA) or settings (eg, community, 31 outpatient clinics 32 ). Even reviews summarising the evidence about the impact of vision on quality of life have usually focused on specific age groups (eg, children, 33 34 older adults 35 ), eye conditions (eg, glaucoma, 36 diabetic retinopathy, 37 dry eye 38 ) or interventions (eg, low vision rehabilitation for children, 34 anti-vascular endothelial growth factor therapy for age-related macular degeneration 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…The visual impairment (VI) is characterized by a condition of low vision or blindness, which may result from a disease, trauma, congenital or degenerative condition [1,2]. Both moderate and severe VI are grouped and classified as low vision, which together with blindness represents all vision impairments [3].…”
Section: Introductionmentioning
confidence: 99%